Sedimentary patterns and palaeoceanography of the Albian Marne a Fucoidi Formation (Central Italy) revealed by high‐resolution geochemical and nannofossil data. Issue 1 (28th July 2016) - Giorgioni, Martino; Tiraboschi, Daniele; Erba, Elisabetta; Hamann, Yvonne; Weissert, Helmut
Abstract: The pelagic Marne a Fucoidi Formation from the Umbria–Marche Basin (Central Italy) is one of the best‐preserved deep‐marine archives of the Aptian–Albian. Frequent changes in lithology, from black to green and red marlstones and limestones, record fluctuating oceanographic and climatic conditions during the deposition of these sediments. Here, the lithological changes in the Albian of the Marne a Fucoidi Formation are studied with unprecedented resolution using X‐ray fluorescence core scanning measurements of major and minor element abundances, as well as statistical analyses of calcareous nannofossil indices. The results obtained with these two independent methodologies are in good agreement and allow for improving the understanding of the peculiar palaeoceanographic conditions of the western Tethys during the Albian. Black shale–marlstone couplets were driven by orbitally forced changes in physical oceanography, resulting in oxygen‐depleted bottom water at times of decreased mixing of shallow water masses. On the other hand, red marlstones represent episodes of enhanced oxygenation at the bottom, probably due to the influence of deep waters from the eastern Tethys. Overall, the Marne a Fucoidi Formation is the expression of highly variable oceanographic conditions related to an unstable Albian circulation mode.